-0.6x+0.7x-1=1

Simple and best practice solution for -0.6x+0.7x-1=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.6x+0.7x-1=1 equation:


Simplifying
-0.6x + 0.7x + -1 = 1

Reorder the terms:
-1 + -0.6x + 0.7x = 1

Combine like terms: -0.6x + 0.7x = 0.1x
-1 + 0.1x = 1

Solving
-1 + 0.1x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 0.1x = 1 + 1

Combine like terms: -1 + 1 = 0
0 + 0.1x = 1 + 1
0.1x = 1 + 1

Combine like terms: 1 + 1 = 2
0.1x = 2

Divide each side by '0.1'.
x = 20

Simplifying
x = 20

See similar equations:

| 24-3x=-7(3-6x) | | t^6+6t^3=27 | | -7.7-4y-7.7-2y=-5y-7.5 | | (x-4)*(x+3)=(x-2)*(x-1) | | 3+7(2-5)+4= | | 3x-150=-450 | | 3.5x=4.7 | | -1/10(10)+4= | | -(1-1)+3= | | .25w+2.5=.5w+1.33 | | 2x-52+5x=46 | | (9q^5-9q^4-3)+(2q^5+4q-1)= | | 2x^3-3x^2+12x-18=0 | | 3(2+x)=18 | | y+2=0.6(x-1) | | 5x+10y-12z=0 | | 9x+2-5x=10+3x+1 | | 1.25v+16=.833v+14 | | -(1-0)+3= | | x+3x+9-5x=180 | | 6m(m+3n+1)= | | 79-x=40 | | y=mx+bwhatism | | 6t^2-2t+2=4t^2 | | (7w-4)-(w+3)= | | 3y+5=5y-3y | | -(1-0)3= | | X^2+15-16=0 | | 2(18+-6y)-3y=-24 | | 5n+8=-(2-6n)+8 | | 3xsquared=6-9x | | 8x+12+9(2x-4)= |

Equations solver categories